Model Pembelajaran Discovery Learning dalam Meningkatkan Hasil Belajar Peserta Didik Sekolah Dasar di Indonesia - Saud, Abdul Mu’min; Fazrin, Lutfia Ainun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the relationship of the discovery learning model to the learning outcomes of students in elementary schools. The method used in this research is qualitative, so it will produce descriptive data. The type of research in this research is library research, which is a series of activities related to collecting library data by exploring, observing, analyzing, identifying knowledge, reading and taking notes, and processing research materials sourced from books, journals, notes. , reports, encyclopedias, research results, and other relevant sources. Data analysis in this study used data reduction, data presentation, and conclusion drawing. As well as data collection techniques in this study using documentation and literature study. The results of the analysis that have been carried out provethat there is a relationship between student learning outcomes and the discoery learning model, this is evident in the results of previous studies. The application of the discovery learning model will succeed in improving student learning outcomes if the appropriate discovery learning model steps are used. The steps of the discovery learning model include providing stimulation, identifying problems, collecting data, processing data, proving and drawing conclusions.